Investigating the structure–function relationship in triple cation perovskite nanocrystals for light-emitting diode applications. Issue 34 (3rd August 2020) - Vashishtha, Parth; Veldhuis, Sjoerd A.; Dintakurti, Sai S. H.; Kelly, Nicole L.; Griffith, Benjamin E.; Brown, Alasdair A. M.; Ansari, Mohammed S.; Bruno, Annalisa; Mathews, Nripan; Fang, Yanan; White, Tim; Mhaisalkar, Subodh G.; et al.
Abstract : Novel Cs-containing triple cation perovskite nanocrystals produce high-performance LEDs as a result of improved surface passivation and environmental stability. Abstract : Organic metal halide perovskite nanocrystals are promising candidates for light-emitting diodes due to their narrow emission bandwidth, high photoluminescence quantum yield (PLQY), and color tunability. Nevertheless, these systems suffer from thermal instability, phase impurities, and a sensitivity to processing techniques. This study reports the first synthesis of novel Cs-containing triple cation perovskite nanocrystals with nominal stoichiometry Cs x (MA0.17 FA0.83 )1− x PbBr3 ( x = 0–0.15). The effect of Cs + cation incorporation is thoroughly investigated using diffraction, microscopy and solid state MAS NMR techniques. The solid state 133 Cs MAS NMR results reveals the distribution of the Cs + cations is highly concentration and particle size dependent, with maximized surface/subsurface Cs + concentrations being achieved with the smaller 5 mol% Cs system. These characteristics directly correlate improved surface passivation and environmental stability of the triple cation system. These triple cation nanocrystals exhibit a maximum photoluminescence quantum yield of ∼93% which upon translation to nanocrystalline LED devices delivers a maximum EQE of 7.4% (30 cd A −1 ) corresponding to a power efficiency of 34.87 lm W −1 . This performance represents a marked improvement compared to CsPbBr3 nanocrystals (PL quantum yield ∼50%; maximum EQE of 2.5% (7.2 cd A −1 )) fabricated under similar conditions.